INCLUSIVE LIBRARY SERVICES: AN IMPERATIVE FOR ACADEMIC LIBRARIES IN NIGERIA (NAU Journal of Library and Information Science, 2019)
The paper explored the need for inclusive library services in the academic library in Nigeria. Students with disability attend institutions of higher learning and as such need library services just like other students. Although these library services are available to other students, students living with disability cannot easily access them. Hence this paper highlights the benefits of inclusive services in the library.It also discussed the resources needed for such services as well as challenges academic libraries encounter in trying to render inclusive services. The paper equally made recommendation on how to counter such challenges.
Keywords: Inclusive Library Services; Academic libraries; Students with Disabilities